1999
DOI: 10.1126/science.286.5444.1566
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Respiratory Frequency by Peptidergic Input to Rhythmogenic Neurons in the PreBötzinger Complex

Abstract: Neurokinin-1 receptor (NK1R) and mu-opioid receptor (muOR) agonists affected respiratory rhythm when injected directly into the preBötzinger Complex (preBötC), the hypothesized site for respiratory rhythmogenesis in mammals. These effects were mediated by actions on preBötC rhythmogenic neurons. The distribution of NK1R+ neurons anatomically defined the preBötC. Type 1 neurons in the preBötC, which have rhythmogenic properties, expressed both NK1Rs and muORs, whereas type 2 neurons expressed only NK1Rs. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
631
2
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(699 citation statements)
references
References 30 publications
57
631
2
9
Order By: Relevance
“…As an additional metric to assess the postlesion state of the CPG, we exploited previous evidence that SP excites NK1R-expressing preBötC neurons to boost respiratory activity (24). Lesioned preBötC-surface slices exhibited irregular SP-evoked rhythms that were unsustainable (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As an additional metric to assess the postlesion state of the CPG, we exploited previous evidence that SP excites NK1R-expressing preBötC neurons to boost respiratory activity (24). Lesioned preBötC-surface slices exhibited irregular SP-evoked rhythms that were unsustainable (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our current view of respiratory rhythm generation in mammals is that there are two distinct, normally coupled, rhythm generators. The primary site, the preBötC, is ventral to the nucleus ambiguus, midway between the facial nucleus and the obex, caudal to the Bötzinger Complex and rostral to the ventral respiratory group (VRG) in the rostroventrolateral medulla [32,33] . The preBötC is postulated to generate inspiratory rhythmic activity that dominates breathing in mammals at rest [34,35] .…”
Section: Cholinergic Innervation and Nachrs In Brainstem And Spinal Cmentioning
confidence: 99%
“…In this review, we focus on the role of nAChRs in the preBötC, an essential site for respiratory rhythm generation [32][33][34] , and in brainstem and spinal cord respiratory motor nuclei in regulation of respiration.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to define the boundaries of the preBötzC. Studies in adult rats found a distinct increase in NK1R-positive neurons ventral to NA (6,7,34,35). Subsequently, data from other studies suggested that a high density of somatostatin immunoreactive neurons ventral to NA accurately defined the boundaries of the preBötzC (34).…”
Section: Discussionmentioning
confidence: 99%